The Endoscopy Global Rating Scale – Canada: Development And Implementation of a Quality Improvement Tool. (2013) - MacIntosh, Donald; Dubé, Catherine; Hollingworth, Roger; van Zanten, Sander Veldhuyzen; Daniels, Sandra; Ghattas, George
Abstract : BACKGROUND: Increasing use of gastrointestinal endoscopy, particularly for colorectal cancer screening, and increasing emphasis on health care quality highlight the need for endoscopy facilities to review the quality of the service they offer. OBJECTIVE: To adapt the United Kingdom Global Rating Scale (UK-GRS) to develop a web-based and patient-centred tool to assess and improve the quality of endoscopy services provided. METHODS: Based on feedback from 22 sites across Canada that completed the UK endoscopy GRS, and integrating results of the Canadian consensus on safety and quality indicators in endoscopy and other Canadian consensus reports, a working group of endoscopists experienced with the GRS developed the GRS-Canada (GRS-C). RESULTS: The GRS-C mirrors the two dimensions (clinical quality and quality of the patient experience) and 12 patient-centred items of the UK-GRS, but was modified to apply to Canadian health care infrastructure, language and current practice. Each item is assessed by a yes/no response to eight to 12 statements that are divided into levels graded D (basic) through A (advanced). A core team consisting of a booking clerk, charge nurse and the physician responsible for the unit is recommended to complete the GRS-C twice yearly. CONCLUSION: The GRS-C is intended to improve endoscopic services in Canada by providing endoscopy units with a straightforward process to review the quality of the service they provide.